EVALUATING TEACHER’S USE OF L1 IN ENGLISH EDUCATION PROGRAMS FOR UNDERGRADUATES IN CHINA - Ruan Xinbei; Wardatul Akmam Din; Suyansah Swanto; Huang Yanyun (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
This paper delves into the contentious issue of language choice in English as a Second Language (ESL) classrooms, particularly focusing on whether teachers should use students’ first language (L1) or exclusively employ English (L2). The debate surrounding this topic has persisted for years, with proponents of L2 immersion arguing for increased English input to enhance language proficiency, while others advocate for the multifaceted roles L1 can play in the learning process. Adopting questionnaires and a focus group interview to analyze the current state of English teaching for undergraduates in Chinese universities, this study reveals the challenges faced by students, including dissatisfaction with existing teaching methods and their own proficiency levels. The research sheds light on the prevalent bilingual approach employed by teachers, balancing English and Chinese based on specific classroom situations. Despite efforts to implement monolingual classrooms, challenges arise due to linguistic diversity among students and the complexities of teaching intricate concepts solely in English. The paper also examines historical pedagogical methods, emphasizing the use of L1 to facilitate understanding and emotional connection, and contrasting approaches advocating maximal L2 input. By critically assessing language choice based on teaching goals, students’ needs, and contextual factors, educators can strike a delicate balance, fostering linguistic development and preparing students for the globalized world effectively. This study emphasizes the importance of justifying language choices in ESL classrooms, ensuring a conducive learning environment while optimizing language input for students’ benefit.